A SCIENTIFIC REVIEW ON NIDRAJANANA (HYPNOTIC) DRUGS IN AYURVEDA (AYUSHDHARA, 2015)
Ayurveda became gradually acceptable globally due to its holistic approach. Its primary objective is to promote and preserve physical & mental health. For achieving this goal ancient Ayurvedic scholars has given prime importance to Nidra (Sleep) which is mentioned under Tryopasthambha (three pillars of life). A well modulated sleep pattern surely brings delight and longevity to the person. Acharya Charaka has opined ‘who knows well about natural sleep, insomnia and over sleep along with the causes and treatment, is Pranabhisara Vaidya (Ideal Physician). At present sleep and sleep disorders became a global problem due to lifestyle modification. It is responsible for many kinds of physical, mental and social demolition. Hence it seeks to locate the cause of the sleep issues and address them with natural Ayurvedic healing practices. Therefore it’s become obligatory to obtain a proper knowledge of Ayurvedic Nidrajanana drugs. Sleep and sleep disorders are complex phenomenon till now various researches are going on to understand the sleep, sleep disorder and mechanism of action of inducing agents. In present study an approach has taken to find out the mechanism of action of Ayurvedic sleep inducing agents. The Study found out a relation between Oja (vitality) and sleep. The sleep inducing agents are enhancing the stability of Oja (vitality) which is ideal and may be a preferable sleep inducing agent. Further study is required in this regard.